2003
DOI: 10.1074/jbc.c200621200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of HIV-1 Ribonuclease H by a Novel Diketo Acid, 4-[5-(Benzoylamino)thien-2-yl]-2,4-dioxobutanoic Acid

Abstract: Human immunodeficiency virus-type 1 (HIV-1) reverse transcriptase (RT) coordinates DNA polymerization and ribonuclease H (RNase H) activities using two discrete active sites embedded within a single heterodimeric polyprotein. We have identified a novel thiophene diketo acid, 4-[5-(benzoylamino)thien-2-yl]-2,4-dioxobutanoic acid, that selectively inhibits polymeraseindependent RNase H cleavage (IC 50 ‫؍‬ 3.2 M) but has no effect on DNA polymerization (IC 50 > 50 M). The activity profile of the diketo acid is sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
204
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(209 citation statements)
references
References 23 publications
(22 reference statements)
5
204
0
Order By: Relevance
“…DKAs have been reported to be the first active site agents that can effectively inhibit both HIV-1 RNase H and IN functions, or only one of them, in the low micromolar range and that can also inhibit HIV-1 replication in cell-based assays (30,44 (24). Starting from these results, in the present study we synthesized 6 new couples of diketo ester and DKA derivatives with various structural features, to be used as chemical tools in the characterization of RNase H binding modes.…”
Section: Discussionmentioning
confidence: 99%
“…DKAs have been reported to be the first active site agents that can effectively inhibit both HIV-1 RNase H and IN functions, or only one of them, in the low micromolar range and that can also inhibit HIV-1 replication in cell-based assays (30,44 (24). Starting from these results, in the present study we synthesized 6 new couples of diketo ester and DKA derivatives with various structural features, to be used as chemical tools in the characterization of RNase H binding modes.…”
Section: Discussionmentioning
confidence: 99%
“…Another implication of these studies is that inhibitors of HIV-1 RNase H that are currently being identified as antiretroviral agents (30)(31)(32)(33)(34)(35) will enhance resistance to some NRTIs. It will be important to determine whether the anti-RNase H inhibitors under development will antagonize the activity of some NRTIs so that effective antiretroviral combination therapies can be devised.…”
Section: Discussionmentioning
confidence: 99%
“…Full-length wild-type (WT) and two mutant RT proteins (K103N and Y181C) were expressed in Escherichia coli BL21(DE3) cells and purified as described previously (33). The t500 RNA template was made by IBA GmbH (Germany), and the biotinylated DNA primer was made by Integrated DNA Technology (IDT; Coralville, IA).…”
Section: Methodsmentioning
confidence: 99%
“…The full-length WT and 2 mutant RT proteins were expressed in Escherichia coli BL21(DE3) cells and purified as described previously (33). The ECL RT biochemical assay was performed based on the protocol described previously (34).…”
Section: Methodsmentioning
confidence: 99%